The effect of exercise on menstrual symptoms: a randomized controlled trial - Merve Koçak; Ömer Şevgin (BMC Women's Health)
Abstract Background Menstrual symptoms are a prevalent and frequently encountered woman's health condition. This study aimed to examine the effect of exercise on menstrual symptoms, sleep quality, fatigue, and physical activity levels. Methods The study was designed as a randomized controlled trial between September 2023 and December 2023. The study included 54 women aged 18 to 45 years. The participants were allocated to the exercise or the control group using simple randomization with a sealed envelope method. All participants were evaluated with the Menstrual Symptom Questionnaire (MSQ), the Menstrual Distress Questionnaire (MDQ), the Fatigue Severity Scale (FSS), the Pittsburgh Sleep Quality Index (PSQI), and the International Physical Activity Questionnaire-Short Form (IPAQ) before and after treatment. The control group did not receive an exercise program. The exercise group received strengthening, flexibility, and balance exercises. A moderate-intensity aerobic exercise and walking program was implemented at least three days per week. The study spanned three menstrual cycles for each woman and lasted an average of 12 weeks. Results Within-group analysis showed a significant decrease in MSQ (p=0.001), MDQ (menstrual) (p=0.002), FSS (p=0.003), and PSQI (p=0.001) scores after exercise. In contrast, the IPAQ score increased significantly in the exercise group p=0.001). In the control group, a significant decrease was observed only in the MDQ (intermenstrual) score (p=0.915). A comparison of the pre-treatment and post-treatment changes in the exercise and control groups revealed a significant decrease in MSQ (p=0.001), MDQ (menstrual) (p=0.023), and PSQI scores (p=0.001) and an increase in IPAQ scores (p=0.001) in the exercise group compared to the control group. However, the decrease in MDQ (pre-menstrual and intermenstrual) (p=0.626, p=0.348) and FSS scores (p=0.102) were not statistically different between the groups. Conclusions In conclusion, exercise can decrease the menstrual symptoms in women with menstrual symptoms as a primary outcome. Second, exercise can also increase their sleep quality. Therefore, it can be employed as a non-pharmacological adjuvant method to help women manage their symptoms. Trial registration The protocol is registered with http://clinicaltrials.gov/ (17/August/2023, Clinical Trial, NCT06006507).